Implementation of Micro Learning to Improve Digital Literacy among High School Students - David Darwin; Reny Syafrida; Hin Goan Gunawan; Thalita Fitria Nuryanti; Egi Jenal Mutakin (Pascasarjana Universitas Mataram, 2025)
Digital literacy has become an essential competency for secondary school students as they navigate the rapid flow of online information. Preliminary identification at SMA Negeri 67 Jakarta indicated that most students still demonstrated low levels of digital literacy, particularly in evaluating information and using learning applications effectively. This community service program implemented a micro-learning model as a structured, concise, and accessible instructional approach delivered through students' digital devices. The method consisted of needs analysis, micro-learning content development, training sessions, individual mentoring, and evaluation through pre- and post-tests and classroom observations. The results showed a substantial improvement in students' digital literacy, with average scores increasing from 55 to 78. The distribution of student scores also shifted positively, marked by a significant reduction in low-score categories and an increase in high-achievement groups. Beyond cognitive gains, the program enhanced student engagement, independence, and collaborative skills during learning activities. These findings indicate that micro-learning is an effective and contextually appropriate approach for strengthening digital literacy in secondary education, and it holds strong potential for further development as a sustainable digital learning strategy.